2017
DOI: 10.1103/physrevd.95.104016
|View full text |Cite
|
Sign up to set email alerts
|

Causality in 3D massive gravity theories

Abstract: We study the constraints coming from local causality requirement in various 2 + 1 dimensional dynamical theories of gravity. In topologically massive gravity, with a single parity non-invariant massive degree of freedom, and in new massive gravity, with two massive spin-2 degrees of freedom, causality and unitarity are compatible with each other and both require the Newton's constant to be negative. In their extensions, such as the Born-Infeld gravity and the minimal massive gravity the situation is similar an… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
29
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 31 publications
(29 citation statements)
references
References 53 publications
0
29
0
Order By: Relevance
“…It pays to reproduce end extend the results of the above computation-done for null geodesicsto fields following [17]. In particular, the results become more transparent for a massless scalar field (still a test field with no back reaction) propagating in the background shock-wave.…”
Section: Scalar Field In a Shock-wavementioning
confidence: 68%
See 3 more Smart Citations
“…It pays to reproduce end extend the results of the above computation-done for null geodesicsto fields following [17]. In particular, the results become more transparent for a massless scalar field (still a test field with no back reaction) propagating in the background shock-wave.…”
Section: Scalar Field In a Shock-wavementioning
confidence: 68%
“…But this cannot be done with a single chart for the whole spacetime, so, one can choose the y > 0 part to be asymptotically flat in the Cartesian form. For more discussion on this issue, see [17,25]. A careful analysis leads to the following metric profile function with all arbitrary parameters fixed:…”
Section: Causality In Exotic Massive Gravitymentioning
confidence: 99%
See 2 more Smart Citations
“…In a more recent work [34], introducing impulsive gravitational waves generated by null particles in three spacetime dimensions [35], it has been shown that the local causality and unitarity (the absence of ghosts and tachyons at the linearized level) are not in conflict in flat and AdS backgrounds for massive gravity models.…”
Section: Concluding Commentsmentioning
confidence: 99%